Influence of the Season on Armyworm (Spodoptera frugiperda J.E. Smith) Attacks on Some Bio-fortified maize (Zea mays L.) Varieties Introduced in Kisangani Eco-region (Democratic Republic of the Congo) - D. Bangambingo; B.D. Nzawele; C.L. Inkoto; A.K. Lubobo; O. Mubenga; K.N. Ngbolua; G. Monde (Budapest International Research and Critics University, 2022)
The present study was conducted in the Kisangani region of the northeastern Democratic Republic of Congo in 2018-2019. The objective was to evaluate the influence of the seasons in the face of armyworm attacks on the behavior of three new biofortified maize varieties being introduced in the Tshopo Province. These trials were conducted using a split plot design with three replications and the results were analyzed using R Studio version 3.6 statistical software. The results at (p<0.05) show that all three varieties were attacked by armyworms. The overall average incidence was significantly similar to that of the control. During two cropping seasons, the maize varieties tested showed variable armyworm attack rates: Yellow Plata (14.16%) SAM4 VITA/A (18.05%) SAM4 VITA/B (16.44%) and PVA SYN- 18 F2'' (14.66%). As for the variation of attack between seasons, the results of the statistical analysis showed that season B had a higher attack rate (25.54%) than season A (6.11%).